Improved tropoelastin synthesis in the skin by codon optimization and nucleotide modification of tropoelastin-encoding synthetic mRNA - Sonia Golombek; Thomas Hoffmann; Ludmilla Hann; Markus Mandler; Sabine Schmidhuber; Josefin Weber; Young-Tae Chang; Roman Mehling; Andrea Ladinig; Christian Knecht; Johanna Leyens; Christian Schlensak; et al. (Molecular Therapy: Nucleic Acids, 2023)
Loss of elastin due to aging, disease, or injury can lead to impaired tissue function. In this study, de novo tropoelastin (TE) synthesis is investigated in vitro and in vivo using different TE-encoding synthetic mRNA variants after codon optimization and nucleotide modification. Codon optimization shows a strong effect on protein synthesis without affecting cell viability in vitro, whereas nucleotide modifications strongly modulate translation and reduce cell toxicity. Selected TE mRNA variants (3, 10, and 30 μg) are then analyzed in vivo in porcine skin after intradermal application. Administration of 30 μg of native TE mRNA with a me1 Ψ modification or 10 and 30 μg of unmodified codon-optimized TE mRNA is required to increase TE protein expression in vivo. In contrast, just 3 μg of a codon-optimized TE mRNA variant with the me1 Ψ modification is able to increase protein expression. Furthermore, skin toxicity is investigated in vitro by injecting 30 μg of mRNA of selected TE mRNA variants into a human full-thickness skin model, and no toxic effects are observed. Thereby, for the first time, an increased dermal TE synthesis by exogenous administration of synthetic mRNA is demonstrated in vivo. Codon optimization of a synthetic mRNA can significantly increase protein expression and therapeutic outcome.